The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2174/2588778501808010020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Semen Quality in Type 2 Diabetes Mellitus Sudanese Patients Compared to Non-Diabetic Subjects

Abstract: Background: Diabetes leads to metabolic abnormalities. These abnormalities produce problems in a variety of organ systems such as ophthalmopathies, neuropathies, nephropathies, and vasculopathies. Infertility is common in diabetic patients, caused by abnormal semen. Objectives: This study was conducted to check semen quality in diabetic Sudanese patients. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The findings from this study revealed that the mean sperm morphology (Normal forms) of the T2DM & Malaria co-morbidity group was significantly lower when compared to the T2DM-only group and the controls. The decrease observed in the normal forms of sperm morphology of the T2DM & Malaria co-morbidity group agrees with earlier studies that reported a significant reduction in normal sperm morphology [ 3 , 4 ]. Another study conducted by Condorelli and colleagues reported a decrease in normal forms of sperm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings from this study revealed that the mean sperm morphology (Normal forms) of the T2DM & Malaria co-morbidity group was significantly lower when compared to the T2DM-only group and the controls. The decrease observed in the normal forms of sperm morphology of the T2DM & Malaria co-morbidity group agrees with earlier studies that reported a significant reduction in normal sperm morphology [ 3 , 4 ]. Another study conducted by Condorelli and colleagues reported a decrease in normal forms of sperm.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that T2DM affects the fertility of males. Infertility is a disease of the reproductive system which is defined by the inability of couples to conceive after 12 months or more of unprotected regular sexual intercourse [3]. Male infertility could be caused by poor sperm parameters [4] such as reduced sperm motility, sperm concentration and morphology [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that in DM patients, semen volume, sperm concentration, complete sperm motility, progressive sperm motility, and normal sperm morphology were considerably lower than in nondiabetic controls (Zhu et al, 2017). Semen in patients with T2 DM is of low volume, abnormal motility and morphology compared with non-diabetic subjects (Ibrahim et al, 2018). Ali et al (1993) reported a highly important increase in overall sperm count and sperm concentration in type 1 and type 2 DM patients.…”
Section: Discussionmentioning
confidence: 99%